2022
DOI: 10.1038/s41598-022-20344-y
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of adolescent perceived stress and symptoms of depression and anxiety during the COVID-19 pandemic

Abstract: Adolescents might be particularly affected by the drastic social changes as a consequence of the COVID-19 pandemic, given the increased stress-sensitivity and importance of the social environment in this developmental phase. In order to examine heterogeneity during the pandemic, the current study aimed to identify whether subgroups of adolescents could be distinguished based on their levels of perceived stress and symptoms of depression and anxiety. In addition, we examined which prepandemic factors predicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 47 publications
1
10
1
Order By: Relevance
“…Far-reaching socially isolating measures could have a profound effect on mental wellbeing of adolescents, although recent studies show conflicting results. Several studies have shown signs of deteriorating mental health among adolescents during the COVID-19 pandemic [ 20 , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] ], whereas studies from the Netherlands, Sweden, and Canada showed no difference or even a decrease in the incidence of mental health problems in 2020 compared to pre-COVID-19 years in adolescents [ [33] , [34] , [35] , [36] , [37] ]. Since most of these studies were conducted within the first year of the COVID-19 pandemic, the study period could have been too short to observe robust changes in mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Far-reaching socially isolating measures could have a profound effect on mental wellbeing of adolescents, although recent studies show conflicting results. Several studies have shown signs of deteriorating mental health among adolescents during the COVID-19 pandemic [ 20 , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] ], whereas studies from the Netherlands, Sweden, and Canada showed no difference or even a decrease in the incidence of mental health problems in 2020 compared to pre-COVID-19 years in adolescents [ [33] , [34] , [35] , [36] , [37] ]. Since most of these studies were conducted within the first year of the COVID-19 pandemic, the study period could have been too short to observe robust changes in mental health.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic increased the risk for psychological distress among adolescents, likely due to pandemic-related changes such as isolation from peers and an increased responsibility within the home (Magson et al, 2021;Racine et al, 2021). Previous research in adolescents demonstrated that having problems in the process of identity formation before the pandemic predicted higher levels of anxiety and depressive symptoms during the pandemic (van Loon et al, 2022). In light of these findings, we theorize that prepandemic vulnerabilities, such as the history of child maltreatment, can undermine identity development.…”
Section: Identity and Affect Development During The Covid-19 Pandemicmentioning
confidence: 99%
“…Lastly, we tested the moderating effect of COVID-19-related stress on the association between identity confusion and negative affect. Based on previous research (Fioretti et al, 2020;Scott et al, 2014;van Loon et al, 2022), we expected that COVID-19-related stress would exacerbate the link between identity confusion and increased negative affect over time (see Figure 1 for the conceptual model).…”
Section: The Present Studymentioning
confidence: 99%
“…However, such cross-sectional studies do not allow the examination of potentially distinct trajectory groups of stress developments over time. To our knowledge, the only published longitudinal investigation employing a person-centered approach for the examination of changes in perceived stress levels during the pandemic has been conducted among adolescents [age 12–15 years, ( 16 )]. This study found no support for distinct trajectories of perceived stress.…”
Section: Introductionmentioning
confidence: 99%